Impacts of severe residential wood burning on atmospheric processing, water-soluble organic aerosol and light absorption, in an inland city of Southeastern Europe. (1st July 2022) - Kaskaoutis, D.G.; Grivas, G.; Oikonomou, K.; Tavernaraki, P.; Papoutsidaki, K.; Tsagkaraki, M.; Stavroulas, I.; Zarmpas, P.; Paraskevopoulou, D.; Bougiatioti, A.; Liakakou, E.; Gavrouzou, M.; et al.
Abstract: This study examines the concentrations and characteristics of carbonaceous aerosols (including saccharides) and inorganic species measured by PM2.5 filter sampling and a multi-wavelength Aethalometer during two campaigns in a mountainous, medium-sized, Greek city (Ioannina). The first campaign was conducted in summer and used as a baseline of low concentrations, while the second took place in winter under intensive residential wood burning (RWB) emissions. Very high winter-mean OC concentrations (26.0 μg m −3 ) were observed, associated with an OC/EC ratio of 9.9, and mean BCwb and PM2.5 levels of 4.5 μg m −3 and 57.5 μg m −3, respectively. Simultaneously, record-high levoglucosan (Lev) concentrations (mean: 6.0 μg m −3 ; max: 15.9 μg m −3 ) were measured, revealing a severely biomass burning (BB)-laden environment. The water-soluble OC component (WSOC) accounted for 56 ± 9% of OC in winter, exhibiting high correlations (R 2  = 0.93–0.97) with BB tracers (nss-K +, BCwb, Lev), nitrate and light absorption, potentially indicating the formation of water-soluble brown carbon (BrC) from fast oxidation processes. The examination of diagnostic ratios involving BB tracers indicated the prevalence of hardwood burning, while the mean Lev/OC ratio (22%) was remarkably higher than literature values. Applying a mono-tracer method based on levoglucosan, we estimated very high BB contributions to OC (∼92%), EC (∼64%) and WSOC (∼87%) during winter. On the contrary, low levels were registered during summer for all carbonaceous components, with winter/summer ratios of 4–5 for PM2.5 and BC, 10 for OC, 30 for BCwb and ∼1100 for levoglucosan. The absence of local BB sources in summer, combined with the photochemical processing and aging of regional organic aerosols, resulted in higher WSOC/OC fractions (64 ± 13%). The results indicate highly soluble fine carbonaceous aerosol fraction year-round, which when considered alongside the extreme concentration levels in winter can have important implications for short- and long-term health effects. Graphical abstract: Image 1 Highlights: PM2.5 chemical characterization in a semi-mountainous city of Southeast Europe. Severe PM2.5, OC and levoglusocan levels are found due to wood burning in winter. Biomass burning contributes 92%, 87%, 64% to OC, WSOC, EC, respectively in winter. High levoglucosan-to-OC ratio (22%) is found for local hardwood burning emissions. Fresh wood burning aerosols were highly water-soluble with implication for toxicity.